2021
DOI: 10.3390/genes12050683
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal Subregion and Gene Detection in Alzheimer’s Disease Based on Genetic Clustering Random Forest

Abstract: The distinguishable subregions that compose the hippocampus are differently involved in functions associated with Alzheimer’s disease (AD). Thus, the identification of hippocampal subregions and genes that classify AD and healthy control (HC) groups with high accuracy is meaningful. In this study, by jointly analyzing the multimodal data, we propose a novel method to construct fusion features and a classification method based on the random forest for identifying the important features. Specifically, we constru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 48 publications
1
2
0
Order By: Relevance
“…The importance of hippocampal subfields as a sensitive biomarker for the early detection of dementia has been gradually realized. Different subtypes of dementia have been found to exhibit specific atrophy of hippocampal subfields [17,34,37]. In our study, different hippocampal subregions and even different parts of one hippocampal subregion (head and body) showed distinct volumetric vulnerability.…”
Section: Discussionsupporting
confidence: 46%
“…The importance of hippocampal subfields as a sensitive biomarker for the early detection of dementia has been gradually realized. Different subtypes of dementia have been found to exhibit specific atrophy of hippocampal subfields [17,34,37]. In our study, different hippocampal subregions and even different parts of one hippocampal subregion (head and body) showed distinct volumetric vulnerability.…”
Section: Discussionsupporting
confidence: 46%
“…How to scientifically and effectively integrate genetic data is worth further investigation. In other papers, genetic data has been used to construct fusion features [42][43][44], leading to satisfactory accuracy. In this paper, we extracted 24 genes associated with AD [20] and calculated the eigenvalues of the matrix formed by the corresponding SNPs.…”
Section: Discussionmentioning
confidence: 99%
“…This indicated that the difference of data in each group was amplified by jointly analyzing imaging and genetic data. Some researchers used the gene data to fuse features in other methods [ 23 , 24 , 25 ] and obtained satisfactory classification performance. In this study, we selected the GWAS results associated with AD to construct a matrix and calculated the eigenvalues to adjust the imaging features.…”
Section: Discussionmentioning
confidence: 99%